“Who’s the next einsteingen?”: Evaluating a gamified Project-Based Learning model for TPACK development and user satisfaction in physics teacher preparation - Yudi Guntara; Sohibatul Rizqiah; Aden Yusril Sasmita; Yoni Yoni; Bunga Kusuma Putri; Febri Sahara; Salwa Nurfitriandini; Muhammad Rayhan Dwi Ernanda (Universitas Sultan Ageng Tirtayasa, 2026)
Physics teacher education is faced with the challenge of equipping prospective teachers with TPACK competencies and skills to design learning media that are relevant to Generation Z. This study aims to evaluate the effectiveness of gamification-integrated Project-Based Learning (PBL) programs through the production of educational game show media